THE DEVELOPMENT OF AN INSTRUCTIONAL MODEL TO ENHANCE COMPETENCY FOCUSING ON THAI LANGUAGE COMMUNICATIONS OF GENERAL EDUCATIONAL COURSES FOR UNDERGRADUATE STUDENTS - Masard, Poraphat; Anaman, Apirak; Khaninphasut, Purimpratch; Lekvilai, Supawan (Thai Interdisciplinary and Sustainability Review, 2023)
The purposes of this research were to study the composition of Thai communication competencies and competencies general education and to develop and study the effectiveness of instructional model for undergraduate students. The research result is showed as follows: 1) The composition of learning and teaching should consist of the principle, objectives, contents, the processes of learning, measurement, and evaluation. 2) The improved instructional model should consist of the steps of teaching and learning management via “IKSAR Model” 3) The effectiveness of the instructional model was divided into three competencies: theoretical competence, practical competence, and attributes competency. The effectiveness of the instructional model was found that the achievement of measurement and evaluation both before and after studying was affected as standard of E1/E2 at 86.10/87.33 that the values were greater than specified criteria at 85/85, and the comparison of test results were found that the posttest exam was greater than the pretest exam.